Case Report: Novel Mutations in the PCCB Gene Causing Late-Onset Propionic Acidemia - Ji, Guang; Liu, Yaling; Song, Xueqin; Li, Zhenfei (Frontiers in Genetics, 2022)
Objectives: Propionic acidemia (PA) is an autosomal recessive metabolic disorder caused by the deficiency of the mitochondrial protein propionyl-CoA carboxylase (PCC).Methods: Here we report a patient with PA who was screened by tandem mass spectrometry (MS/MS) and diagnosed by urine gas chromatography mass spectrometry (GC/MS).Results: we used Genetic diagnosis panel to analyze the patient and identified 2 novel mutations in PCCB gene. Disscussion:Screening of organic acid metabolism in blood and urine could be performed so as to avoid misdiagnosis and missed diagnosis.